PENINGKATAN KETERAMPILAN MEMBACA NYARING MELALUI PENGGUNAAN MEDIA PIAS-PIAS KATA - Utami, Muji (Jurnal Likhitaprajna, 2018)
This classroom action research was conducted on first grade students of SD Negeri Coban Blimbing 2 Wonorejo Pasuruan, due to the existence of problems namely the learning outcomes of Indonesian language subjects especially loud reading is still low. Through word-of-mouth media this problem is tried to be improved and improved. The procedure of this study was conducted in two cycles of steps in each cycle consisting of four stages, namely planning, acting, observing and reflecting. Student learning outcomes in the final test presentation of students completing learning in the initial conditions 35.00% became 60.00% in the first cycle increased by 25.00% and became 95.00% and in the second cycle increased 35.00%, the average value the class from the initial condition 57.50 to 70.00 in the first cycle increased 12.50 points and became 81.75 in the second cycle it increased 11.75 points.Keywords: reading skills, reading loud, media of learning